Peningkatan Literasi Bahasa Inggris melalui Program Kampung Inggris Mini di MTs Nadlatut Thalibin - Ekowijayanto, Mochlis; Syarofi, Ibnu; Faiz, M; Sanjaya, Moh. Nunung; Dani, Ahmad (Jurnal Aksi Afirmasi, 2025)
English proficiency at MTs Nadlatut Thalibin, an Islamic boarding school in Tegalwatu Village, Probolinggo Regency, faces significant challenges due to limited exposure and practical use of English in students' daily lives. Conventional teaching methods and the lack of engaging media have resulted in low motivation and skills in English. To address this issue, the KKN Team of Universitas Nurul Jadid implemented the Mini English Village Program, aiming to improve English literacy among students through enjoyable and contextual activity-based learning. This program engaged students in interactive activities such as storytelling, morning talks, English games, and song-based learning. The activities aimed to enhance students' speaking and listening skills while providing them with opportunities to use English practically outside the classroom. Additionally, the program included training for teachers to design more creative and activity-based teaching methods. The evaluation results showed a significant improvement in students' speaking and listening skills. Students, who were previously hesitant, became more active in discussions and quickly absorbed new vocabulary through enjoyable activities. The Mini English Village Program successfully motivated students and provided them with an English learning experience that was applicable and relevant to their daily lives. This program proved to be effective in enhancing English literacy at MTs Nadlatut Thalibin and can serve as a model for other Islamic schools in rural areas.